101 facts about terrarium pets - Barnes, Julia, 1955- (Milwaukee, WI : Gareth Stevens Pub., 2002)
Provides information about different kinds of pets that can live in a terrarium, including turtles, snakes, and lizards, how to care for them, and how to understand their behavior.
Includes bibliographical references (p. ).
Keywords: Reptiles as pets -- Miscellanea -- Juvenile literature; Amphibians as pets -- Miscellanea -- Juvenile literature; Invertebrates as pets -- Miscellanea -- Juvenile literature; Reptiles -- Miscellanea; Amphibians -- Miscellanea; Invertebrates -- Miscellanea; Reptiles as pets; Amphibians as pets; Invertebrates as pets